The PDS 110 observing campaign – photometric and spectroscopic observations reveal eclipses are aperiodic. Issue 2 (29th January 2019) - Osborn, H P; Kenworthy, M; Rodriguez, J E; de Mooij, E J W; Kennedy, G M; Relles, H; Gomez, E; Hippke, M; Banfi, M; Barbieri, L; Becker, I S; Benni, P; et al.
Abstract: PDS 110 is a young disc-hosting star in the Orion OB1A association. Two dimming events of similar depth and duration were seen in 2008 (WASP) and 2011 (KELT), consistent with an object in a closed periodic orbit. In this paper, we present data from a ground-based observing campaign designed to measure the star both photometrically and spectroscopically during the time of predicted eclipse in 2017 September. Despite high-quality photometry, the predicted eclipse did not occur, although coherent structure is present suggesting variable amounts of stellar flux or dust obscuration. We also searched for radial velocity (RV) oscillations caused by any hypothetical companion and can rule out close binaries to 0.1 M s . A search of Sonneberg plate archive data also enabled us to extend the photometric baseline of this star back more than 50 yr, and similarly does not re-detect any deep eclipses. Taken together, they suggest that the eclipses seen in WASP and KELT photometry were due to aperiodic events. It would seem that PDS 110 undergoes stochastic dimmings that are shallower and of shorter duration than those of UX Ori variables, but may have a similar mechanism.